Self-Assessment of experimental and numerical computer models developed at CISMID based on a bench-mark model developed in Japan at 1994 - Rojas, Victor Pool (2019)
This article reports the state-of-the-art of the implementation of finite element modeling for clay masonry walls under lateral loads. Important work had been developed at CIMID Laboratory of Structures in clay walls under lateral loads and, according to the review, nowadays, researches mainly report experimental tests with their numerical nonlinear models. This process is important to validate and complement their results. Bench-mark model developed in 1994 at Chiba University had been selected to evaluate all work developed at CISMID in these recently years.  The evaluation uses three variables: 1) The study evaluated include experimental results for masonry walls, (2) The study evaluated use nonlinear models for interaction between mortar and bricks, and (3) The study evaluated record their results with graphics showing the failure process. Finally, evaluate these models with finite elements demand high costs because the hardware and software requirements. However, the acquisition of a computer for High Performance Computing is necessary to afford this kind of research.